UNRAVELING THE IMPACT OF INTERNET ADDICTION ON QUALITY OF LIFE AMONG NEPALESE UNDERGRADUATES - Kumar Paudel, Ashok; Raj Chhetri, Muni; Devkota, Nishchal; Prasad Ghimire, Murari; Shrestha, Trijya; Kaphle, Maheshor (Journal of Chitwan Medical College, 2024)
Background: The use of the internet has become an integral aspect of our daily lives. Excessive internet usage and internet addiction can significantly impact various dimensions of individuals’ well-being, including social, leisure, economic, and community aspects. This phenomenon is not limited to a particular demographic, as Nepalese youths are also grappling with the repercussions of internet addiction. To explore this issue further, we conducted this study to assess the extent of internet addiction and its impact on the quality of life among undergraduate students in the Kathmandu district of Nepal. Methods: This cross-sectional analytical study involved a randomly selected sample of 307 undergraduate students from four colleges affiliated with Pokhara University in the Kathmandu district of Nepal. Data were gathered through a self-administered structured questionnaire. The Young’s Internet Addiction Test (IAT) and the World Health Organization Quality of Life Brief Version (WHOQOL-BREF) were employed to evaluate internet addiction and quality of life, respectively. Results: The findings revealed that 50% of the students exhibited a mild level of internet addiction, 31.6% demonstrated a moderate level, and 0.7% displayed severe dependence on the internet. The mean quality of life score among respondents was 63.89±11.03. Conclusions: The study highlighted a significant association between internet addiction and the psychological and environmental domains of quality of life. A substantial prevalence of internet addiction was observed among the students, with discernible impacts on their psychological and environmental well-being.